A supercritical fluid extraction process of kenaf seeds - Ismail, Maznah; Chan, Kim Wei; Ghafar, Siti Aisyah (2014)
The present invention provides a supercritical fluid extraction (SFE) process for extracting oil of kenaf seed (Hibiscus cannabin us L.), wherein the SFE process utilises a supercritical fluid and is conducted in a pressure ranging from 200 to 600 bars with a temperature ranging from 40 to 80 DC.